Function outlining and partial inlining - Zhao, Peng; Amaral, J. N. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2005: Anais do XVII International Symposium on Computer Architecture and High Performance Computing, 2005)
Frequently invoked large functions are common in non-numeric applications. These large functions present challenges to modern compilers not only because they require more time and resources at compilation time, but also because they may prevent optimizations such as function inlining. However, usually it is the case that large portions of the code in a hot function f/sub host/ are executed much less frequently than f/sub host/ itself. Partial inlining is a natural solution to the problems caused by including cold code segments that are seldom executed into hot functions that are frequently invoked. When applying partial inlining, a compiler outlines cold statements from a hot function f/sub host/. After outlining, f/sub host/ becomes smaller and thus can be easily inlined. This paper presents a framework for function outlining and partial inlining that includes several innovations: (1) an abstract-syntax-tree-based analysis and transformation to form cold regions for outlining; (2) a set of flexible heuristics to control the aggressiveness of function outlining; (3) several possible function outlining strategies; (4) alias agent, a new technique that overcomes negative side-effects of function outlining. With the proper strategy, partial inlining improves performance by up to 5.75%. A performance study also suggests that partial inlining is not effective on enabling more aggressive in-lining. The performance improvement from partial in-lining actually comes from better code placement and better code generation.